Thought-Shapers Embedded - Kondor, Zsuzsanna (Frontiers in Psychology, 2022)
Accepting the idea that the listed items’ mental representations are thought-shapers, I suggest going a bit further. Accordingly, any kind of representation, be it mental or public (accessible to others), bears thought-shaping potential, albeit not in the same manner. Just as the idea of embodied cognition takes into consideration environmental facilities and obstacles, I suggest investigating thought processes in a wider context, i.e., placing thought-shapers in the context of their formation. I propose that the elements of the above-quoted definition of thought-shapers are built upon a structure which consists of representational skills, means, and institutions. In accordance with the idea of embeddedness and enactment, the need for communication and the given cognitive and physical aptitudes result in different types of expression or representation available to others. When an expressional mode solidifies, it opens up new possibilities and allots limitations. I propose that mundane, almost unnoticeable affordances and their accompanying limits do shape our thoughts thoroughly. In my argument for the thought-shaper potential of public representation and its generative technique, I will delineate a historical overview of representational means in tandem with the main characteristics of different eras’ crucial ideals and patterns of reasoning. I will close the historical overview with a terminological excursion exploring how representation and mental representation relate to each other, and what kinds of ambiguities accompany the use of the latter term. Accordingly, embedding thought-shapers, I will first outline the historical and theoretical background of representation as it emerged in the history of philosophy. Because language is a decisive representational means, I will investigate its orientating and distortive potential. I will rely on some of Bergson’s lesser-known remarks. I will illuminate how ocular-centrism was able to be a decisive metaphor in science and philosophy for long centuries, even recently, and how the concept of mental representation formed philosophical and scientific inquiries.